Market Dynamics in Motion: Exploring the Interplay of Price Volatility, the Activity of Stock Exchange, and its Performance - Salim Djabou (Journal of North African Economies, 2025)
The objective of this study is to analyze the relationship between the activity of emerging stock markets, characterized by high price volatility, and their performance. The case study focuses on the Amman Stock Exchange. Due to the study's nature and its sensitivity in terms of reflection and dynamic correlation, data were collected over three time periods during the year 2022. Multiple statistical models were estimated using statistical and technical tools to analyze the data and uncover the reasons behind the impact of price volatility on the exchange's performance. The Smart PLS4 software was employed for this purpose. The study findings indicate that price volatility are not temporally correlated and have a simultaneous effect on returns. Moreover, these volatility do not influence the behavior of investors in the Amman Stock Exchange, as they do not consider them as a factor in their investment decisions. The study also concludes that the impact of the Amman Stock Exchange's activity on its returns varies depending on the investors' behavior